2018
DOI: 10.1007/s11325-018-1673-z
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pulmonary disease is associated with pain spreading and restless legs syndrome in middle-aged women—a population-based study

Abstract: Introduction Recent studies suggest an increased prevalence of chronic pain conditions and restless legs syndrome (RLS) in patients with chronic pulmonary disease (CPD). We analyzed the prevalence and risk factors for pain and RLS in a populationbased sample of females with comorbid CPD. Method Questionnaire-based data from 2745 women aged 18-64 years were analyzed regarding comorbid CPD status (severe bronchitis, emphysema, asthma). Pain status was assessed according to symptoms reflecting severity (Visual An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…al. showed that chronic pulmonary disease ( emphysema, chronic bronchitis and asthma) is an independent risk factor for RLS. [23] Previous studies have shown that there was no age difference between COPD with RLS and without RLS. [5,6] Similar to these studies, we found that there were no age differences between the two groups.…”
Section: Discussionmentioning
confidence: 94%
“…al. showed that chronic pulmonary disease ( emphysema, chronic bronchitis and asthma) is an independent risk factor for RLS. [23] Previous studies have shown that there was no age difference between COPD with RLS and without RLS. [5,6] Similar to these studies, we found that there were no age differences between the two groups.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have found that restless legs symptoms may have a recurrent affiliation with pain. Widespread pain had been linked to restless legs symptoms in patients with asthma, severe bronchitis, emphysema and they additionally had often tension-type headache, migraine and fibromyalgia (9)(10)(11)(12). The hypothesis assumed either the mechanisms of pain intensity defused restless legs symptoms or the symptoms compounded the sense of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover some patients experienced the symptoms as pain intrinsically without any other source of pain (8). Often restless legs symptoms occur with widespread pain and distressing ailments such as tension-type headaches, migraines and fibromyalgia (9)(10)(11)(12)(13). Knowledge of the pathophysiology and clinical experience of restless legs symptoms have increased during the last decade, but the definite pathophysiology is still not completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…At a more granular level, the relationship between RLS and SDB may be attributable to intermittent hypoxia, as respiratory event-associated hypoxia may cause dysfunction of the dopaminergic pathway [22]. This postulate is supported by the high prevalence (30-40%) of RLS among those with moderate to severe chronic obstructive pulmonary disease (COPD), association of smoking and RLS in epidemiology studies, increased use of inhalative respiratory medications in RLS populations [23], and the clinical experience of worsening RLS with acute exposure to high altitude [24]. Specifically, a 3-fold higher prevalence of RLS has been observed in those with COPD compared to age and sex-matched controls [25].…”
Section: Discussionmentioning
confidence: 99%